Classroom management: A case study of English teaching and learning in a secondary school in Nepal - Arini Sabrina (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2022)
This study investigates the implementation of classroom management at Kanya-CO Education Secondary School Nepal. The investigation covers six points to discuss: the management of the physical environment, learning, procedures and rules, discipline problems, relationships, also voice and body language. Each of these has some characteristics that are compared to those of the classroom observed.The research is categorized as qualitative in nature. It gains the data through video observation showing English teaching and learning process with approximately 40 students. The data are then analyzed based on the criteria aforementioned. Overall, the teacher has applied the postulates thoroughly. However, some weaknesses related to the management of the physical environment, learning, and relationships keep remaining. Accordingly, the paper also provides the suggestions to consider as the teaching and learning process improvement exertion.